Two new species of semiaquatic freshwater crabs of the genera Tortomon and Aiyunamon from karst forests in northern Vietnam (Crustacea: Brachyura: Potamidae) - Ng, Peter K. L.; Tri, Ngo Van (Zootaxa, 2023)
Two new genera of freshwater crabs (Potamidae) are recorded from northern Vietnam, Tortomon Huang, Wang & Shih, 2020, and Aiyunamon Pan, Ng & Sun, 2022. These genera had previously only been reported from southern China and eastern Myanmar. Each genus is represented by a new species. Tortomon distinctum n. sp. is markedly different from its two Chinese congeners in its proportionately wider carapace, more elongate third maxilliped, the carpus of the cheliped being armed only with a low tubercle, possessing relatively more slender and longer ambulatory legs, a gently curved male first gonopod and a more elongate male second gonopod. Aiyunamon vietnamicum n. sp. is distinct from its five congeners in its proportionately less convex dorsal surface of the carapace, relatively lower epigastric cristae, lower rugosities of the postorbital cristae, wider median lobe of the posterior margin of the epistome, relatively narrower male pleon, and a male first gonopod that has the terminal segment more distinctly curved with a wider concavity on the outer margin of the subterminal segment.